The effect of the questions students have learning model assisted by interactive poster media on learning outcomes in the cognitive domain of science - Oktorin, Yuda; Sumarli, Sumarli; Mulyani, Sri (ORBITA: Jurnal Pendidikan dan Ilmu Fisika, 2024)
This research aims to describe the influence of the Questions Student Have learning model assisted by interactive poster media on learning outcomes in the cognitive science domain of fifth grade elementary school students. The type of research used is quantitative research with a quasi-experimental design, and a post-test only control group design. The population of this research was class V students at SDN 84 Singkawang, totaling 43 students using a saturated sampling technique so that the sample used was 43 students consisting of VA as the control class and VB as the experimental class. The data collection technique used in this research is a test technique in the form of a cognitive domain learning outcomes test and a non-test in the form of a student response questionnaire. The data analysis technique used is quantitative analysis in the form of independent sample t-test, effect size and descriptive percentage. The results of the research show that: (1) There are differences in students' cognitive learning outcomes in science learning in class V elementary school between classes that use the Questions Student Have learning model assisted by interactive poster media and classes that use direct learning. This is shown by the significance level between the experimental classes of 0.002 > 0.05. (2) The Questions Student Have learning model assisted by interactive poster media has a high influence on students' cognitive learning outcomes in science learning in class V elementary school. This is shown by the Effect Size results of 0.993. (3) Positive student responses to the Questions Students Have learning model in science learning in fifth grade elementary school. This is shown from the calculations that the percentage of student responses of 80.5% is included in the very good category. So the conclusion of this research shows that there is an influence of the Questions Student Have learning model assisted by interactive poster media on learning outcomes in the cognitive science domain of fifth grade elementary school students.